(untitled) (Research, Society and Development, 2021)
Childhood obesity is considered one of the most serious and main public health problems in the entire planet, affecting millions of children in Brazil and in the world. It is a multifactorial health problem resulting from hormonal, metabolic, genetic, behavioral and even cultural problems. It can cause other serious diseases such as cardiovascular, neoplastic and metabolic diseases, among others. Faced with this serious problem, the study aims, through a literature review, to verify the importance of identifying and preventing obesity from childhood, thus avoiding a series of complications arising from excess body fat at this stage or in adulthood. In this work, the factors that cause obesity, its consequences, the complications that this disease can cause and the role of physical activity and nutrition in preventing obesity were reported. It was confirmed that the earlier obesity is detected, the greater the success in reversing the condition. Studies currently show that in most cases, physical exercise combined with a balanced diet through good nutrition are the best option to combat obesity.